THE EXISTING CONDITION OF THE DRIED SALTED FISH SUPPLY CHAIN IN SIBOLGA CITY, NORTH SUMATRA - Irwan Limbong; Muhammad Yogi Prayoga; Amraini Fitri; Andrha Syatha Pahana (Asian Journal of Aquatic Sciences, 2025)
Sibolga City is one of the coastal areas in North Sumatra Province that plays a vital role in Indonesia’s marine and fisheries sector. This study aims to analyze the supply chain system of dried salted fish in Sibolga City, which includes three main components: the product flow, information flow, and financial flow. The research was conducted in September 2025 using a descriptive method with a mixed quantitative and qualitative approach. Primary data were obtained through interviews and field observations involving fishermen, dried salted fish processors, collectors, retailers, and the Department of Marine Affairs and Fisheries (DKP) of Sibolga City. In contrast, secondary data were derived from DKP reports. The results showed that there are three main supply chain patterns: (1) fisherman–processor–collector–retailer–consumer, (2) fisherman–processor–collector–consumer, and (3) fisherman–processor–direct consumer. On average, dried salted fish processors in Sibolga can produce between 100 and 200 kg per day, depending on the availability of raw materials. Shorter distribution channels generate higher efficiency by reducing marketing costs, accelerating the flow of information and finance, and maintaining product quality. This study concludes that the dried salted fish supply chain in Sibolga City has been functioning but remains sub-optimal. Strengthening coordination among actors, improving access to formal financing, and utilizing information technology in distribution and marketing are necessary to enhance efficiency and increase the added value of dried salted fish products at the local level.